EXPERT SYSTEM TO IDENTIFY STUDENTS BEHAVIOR AND PERSONALITY IN SMK NEGERI 2 TANGERANG - Fifit Alfiah; Muhammad Arba Adnandi; Allyufi Fazril Rasyidin (Jurnal Techno Nusa Mandiri, 2019)
The number of problems in learning activities such as the personality and behavior of students who are less good towards the teacher and there is still many students who are confused in their personality in deciding to continue their studies with a department in accordance with their education or personality. So the author aims to create one expert system that can help counseling and student teachers in determining personality and good behavior for students who are not good or to determine in continuing college studies with one of the knowledge that can help humans in making decisions, namely expert systems. Expert system (Expert System) is a part of artificial intelligence that contains knowledge and experience that is input into the knowledge base. In designing this expert system, the author uses a forward chaining technique because problem-solving is done by collecting data and then drawing a conclusion. The results of this expert system are able to help psychology or Counseling Guidance teachers in analyzing student behavior to improve quality human resources by testing the diagnosis of student behavior and personality with expert system applications to produce solutions that meet their needs with a percentage above 90%.